PENGARUH MODELLING THE WAY TERHADAP KEMAMPUAN MENULIS TEKS CERITA FABEL SISWA SMP - Octavia Lestari P. (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2017)
The Effect of Modeling the Way on Ability to Write Text of Fables of Junior High School Students. This study aims to determine the effect of modeling model learning the way to the ability to write text stories fable junior high school students. The research used quantitative approach with experiment method. The population of this study is the students of class VIII SMP Muhammadiyah 3 Medan, amounting to 50 people. Data collection is done through learning result test. The results showed the ability to write fable story text by using modeling modeling the way in experiment class good categorized and there is influence model of learning modeling the way to the ability of writing fable story text by grade VIII student of SMP.